Eksplorasi Teks Budaya Hindu di Lereng Gunung Rahung Kabupaten Banyuwangi Kajian Antropolinguistik - Sutama, I Putu; Suteja, I Wayan (Humanis; Vol 28 No 1 (2024), 2024)
One of the ethnic groups that has a long cultural history is the Javanese ethnic group that inhabits on a Mountain Slopes - Raung in the Banyuwangi Regency, East Java. The Javanese ethnic group on the slopes of Mountain Raung is considered that have already known yulis reading since Majapahit kingdom, and therefore this Javanese ethnic group has cultural remained in the form of writing which were known as Cultural texts. The analysis used a qualitative descriptive research. Researchers used an anthropolinguistic perspective or theoretical framework which viewed that text was a cultural phenomenon which was an activityof the language use, language is the main focus of study, which was always connected to the cultural context. The results of the research were the text forms that preferred were (1) oral text forms, (2) written text forms, and (3) symbolic text forms. Noun category, namely Attributive Noun Phrases which had the structure Noun (N1) + Noun (N2). Then, written text was text written on a certain media such as signboards and nomenclature. Then, simbolic text was text that stored in cultural artifacts or sites such as temples, padmasana, and statues.